Kompresi File Menggunakan Algoritma Lempel Ziv Welch (LZW) - Aries Suharso (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2020)
AbstractIn the field of information technology, data communication is closely related to file delivery. The size of the file is sometimes a constraint in the delivery process. Large files will take longer delivery times compared to files with smaller sizes. Therefore, to handle the problem, one of them by means of compression. This research uses the Software Development Life Cycle (SDLC) method with waterfall models with analysis, design, coding and testing. This app was built using the Lempel Ziv Welch (LZW) algorithm. The Lempel Ziv Welch (LZW) algorithm is included in the lossless compression technique, which is a compression technique that does not alter the original data. The result of a compression assessment used the Lempel Ziv Welch (LZW) algorithm shows the average rate of compression ratio and for all types of text files by 51.04% with an average of 2.56 seconds, for an image file type of 37.26% with an average time of 0.44 seconds. Based on the average percentage of the compression ratio for all file types tested using the LZW algorithm (Lemp Ziv Welch) is 40.40% with an average time required is 1.81 seconds.